Pengembangan Perangkat Pembelajaran Sepakbola Berbasis Aplikasi Articulate Storyline - Gunawan, Dimas Chandra; Hari Wiguno, Lokananta Teguh; Kurniawan, Ari Wibowo; Mu’arifin, Mu’arifin (Sport Science and Health, 2021)
Abstract: Research product development is aimed at developing a soccer learning device based on the application articulate storyline for the physical education working group elementary school in Sumbermanjing Wetan District, Malang Regency. This study uses the Research and Development method or development research. Subjects for small group trials involved 10 primary school PJOK teachers and subjects for large groups involved 41 primary school PJOKs, namely the Teacher Working Group (KKG) in Sumbermanjing Wetan District. Obtained from data analysis, namely with a percentage of 94% of learning experts, 97% of elementary game experts, 89% of physical education, sports and health experts, 99% of media experts, 95% of soccer experts, 88% the results of trial I, the percentage of 86% of the results of trial II. The conclusion in this development research is that the application development product articulate storyline is suitable to be used as a support in learning football. Abstrak: Penelitian produk pengembangan yaitu bertujuan mengembangkan perangkat pembelajaran sepakbola berbasis aplikasi articulate storyline untuk KKG PJOK SD di Kecamatan Sumbermanjing Wetan, Kabupaten Malang. Penelitian ini menggunakan metode Research and Development atau penelitian pengembangan. Subjek untuk uji coba kelompok kecil melibatkan 10 guru PJOK SD dan subjek untuk kelompok besar melibatkan 41 PJOK SD yaitu Kelompok Kerja Guru (KKG) di Kecamatan Sumbermanjing Wetan. Didapat dari analisis data yaitu dengan persentase 94% dari ahli pembelajaran, persentase 97% ahli permainan SD, persentase 89% dari ahli pendidikan jasmani, olahraga dam kesehatan dengan, persentase 99% dari ahli media, persentase 95% dari ahli sepakbola, persentase 88% hasil uji coba I, persentase 86% hasil uji coba II. Kesimpulan dalam penelitian pengembangan ini yaitu produk pengembangan aplikasi articulate storyline ini layak dipergunakan sebagai penunjang dalam pembelajaran sepakbola.